Analisis Minat Belajar Matematika Mahasiswa pada Mata Kuliah Kalkulus - Sukma Hardana; Hasanuddin . (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
This study aims to describe students' learning interest in the Calculus course. Learning interest is an important affective factor that supports students' ability to understand abstract and complex mathematical concepts. This research used a quantitative descriptive approach with a survey method. The respondents were Mathematics Education students who had taken Calculus. Data were collected through a non-test questionnaire distributed online using Google Form. The questionnaire measured four indicators: enjoyment, interest, attention, and student involvement. The data were analyzed using percentage calculations and categorized based on predetermined criteria. The results showed that students' overall learning interest was 44.6%, which belonged to the moderate category. These findings indicate that students' interest in learning Calculus is not yet optimal, so more interactive, contextual, and varied learning strategies are needed to strengthen motivation and engagement.